Epidemiology of severe acute respiratory illness (SARI) among adults and children aged ≥5 years in a high HIV-prevalence setting, 2009-2012. - Cheryl Cohen; Sibongile Walaza; Jocelyn Moyes; Michelle Groome; Stefano Tempia; Marthi Pretorius; Orienka Hellferscee; Halima Dawood; Summaya Haffejee; Ebrahim Variava; Kathleen Kahn; Akhona Tshangela; et al. (PLoS ONE)
Objective There are few published studies describing severe acute respiratory illness (SARI) epidemiology amongst older children and adults from high HIV-prevalence settings. We aimed to describe SARI epidemiology amongst individuals aged ≥5 years in South Africa. Methods We conducted prospective surveillance for individuals with SARI from 2009-2012. Using polymerase chain reaction, respiratory samples were tested for ten viruses, and blood for pneumococcal DNA. Cumulative annual SARI incidence was estimated at one site with population denominators. Findings We enrolled 7193 individuals, 9% (621/7067) tested positive for influenza and 9% (600/6519) for pneumococcus. HIV-prevalence was 74% (4663/6334). Among HIV-infected individuals with available data, 41% of 2629 were receiving antiretroviral therapy (ART). The annual SARI hospitalisation incidence ranged from 325-617/100,000 population. HIV-infected individuals experienced a 13-19 times greater SARI incidence than HIV-uninfected individuals (p<0.001). On multivariable analysis, compared to HIV-uninfected individuals, HIV-infected individuals were more likely to be receiving tuberculosis treatment (odds ratio (OR):1.7; 95%CI:1.1-2.7), have pneumococcal infection (OR 2.4; 95%CI:1.7-3.3) be hospitalised for >7 days rather than <2 days (OR1.7; 95%CI:1.2-2.2) and had a higher case-fatality ratio (8% vs 5%;OR1.7; 95%CI:1.2-2.3), but were less likely to be infected with influenza (OR 0.6; 95%CI:0.5-0.8). On multivariable analysis, independent risk indicators associated with death included HIV infection (OR 1.8;95%CI:1.3-2.4), increasing age-group, receiving mechanical ventilation (OR 6.5; 95%CI:1.3-32.0) and supplemental-oxygen therapy (OR 2.6; 95%CI:2.1-3.2). Conclusion The burden of hospitalized SARI amongst individuals aged ≥5 years is high in South Africa. HIV-infected individuals are the most important risk group for SARI hospitalization and mortality in this setting.